2022
DOI: 10.3390/s22197687
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach to Predict the Performance of a Stratified Thermal Energy Storage Tank at a District Cooling Plant Using Sensor Data

Abstract: In the energy management of district cooling plants, the thermal energy storage tank is critical. As a result, it is essential to keep track of TES results. The performance of the TES has been measured using a variety of methodologies, both numerical and analytical. In this study, the performance of the TES tank in terms of thermocline thickness is predicted using an artificial neural network, support vector machine, and k-nearest neighbor, which has remained unexplored. One year of data was collected from a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The high applicability of ANN for simulating multi-parameter systems has received significant attention in many different fields (e.g., color coordinates in dyeing [7], energy storage tanks [8], and concrete [9,10]). Details of ANN and other soft computing technologies applications on mining engineering can be found in Jang and Topal (2014) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The high applicability of ANN for simulating multi-parameter systems has received significant attention in many different fields (e.g., color coordinates in dyeing [7], energy storage tanks [8], and concrete [9,10]). Details of ANN and other soft computing technologies applications on mining engineering can be found in Jang and Topal (2014) [11].…”
Section: Introductionmentioning
confidence: 99%
“…By rotating the folds, cross-validation permits a comprehensive evaluation of the model across the entire dataset, minimizing the risk of overfitting. Accuracy, precision, recall, and F1 score are performance metrics computed by aggregating the outcomes from each iteration, providing a dependable estimate of the classifier's performance on unseen data [37][38][39][40]. Interestingly, we implemented the k-fold cross-validation technique to prevent overfitting with the k set to five.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…There are various machine learning models that can be employed to learn the flow patterns in urban areas. In this work, we tried several methods of computational learning; the methods were tested according to their level of accuracy, and the method found to have the highest accuracy is the kNN method [28]. The kNN method can be based on different values of K; we found that setting the value to 6 gives the appropriate balance between the calculation time and the desired accuracy.…”
Section: Machine Learningmentioning
confidence: 99%